Naso-Orbito-Ethmoid Fibrous Dysplasia, a Rare Case in a Rare Location for Radiologists: A Case Report - Regmi, Pradeep R; Kayastha, Prakash; Amatya, Isha (Journal of Institute of Medicine Nepal, 2022)
Fibrous dysplasia is a non-inherited but congenital disorder which is characterised by the replacement of normal bone by an excessively proliferative cellular fibrous connective tissue intermixed with irregular bony trabeculae. Fibrous dysplasia may be localised to the single bone (monostotic form) or multiple bones (polyostotic form). About 25-30% of the facial dysplasia is associated with cranial or facial involvement. Imaging plays an important role in diagnosis and follow-up in the cases of cranio-facial fibrous dysplasia because of the anatomical complexity of the region. We have described herein a rare case of fibrous dyplasia involving naso-orbito-ethmoid region in radiological perspective.